HSPA5 negatively regulates lysosomal activity through ubiquitination of MUL1 in head and neck cancer. Issue 3 (4th March 2018) - Kim, Sun-Yong; Kim, Hyo Jeong; Kim, Haeng-Jun; Kim, Dae Ho; Han, Jae Ho; Byeon, Hyung Kwon; Lee, Keunho; Kim, Chul-Ho
ABSTRACT: HSPA5/GRP78/BiP plays an important role in cell survival or tumor progression. For these reasons, HSPA5 is an emerging therapeutic target in cancer development. Here we report that HSPA5 contributes to head and neck cancer (HNC) survival via maintenance of lysosomal activity; however, a nonthermal plasma (NTP, considered as a next-generation cancer therapy)-treated solution (NTS) inhibits HNC progression through HSPA5-dependent alteration of lysosomal activity. HSPA5 prevents NTS-induced lysosome inhibition through lysosomal-related proteins or regulation of gene expression. However, NTS-induced MUL1/MULAN/GIDE/MAPL (mitochondrial ubiquitin ligase activator of NFKB 1) leads to downregulation of HSPA5 via K48-linked ubiquitination at the lysine 446 (K446) residue. MUL1 knockdown hinders NTS-induced lysosome inhibition or cytotoxicity through the reduction of HSPA5 ubiquitination in HNC cells. While MUL1 was suppressed, HSPA5 was overexpressed in tissues of HNC patients. NTS strongly inhibited HNC progression via alterations of expression of MUL1 and HSPA5, in vivo in a xenograft model. However, NTS did not induce inhibition of tumor progression or HSPA5 reduction in MUL1 knockout (KO) HNC cells which were generated by CRISPR/Cas9 system. The data provide compelling evidence to support the idea that the regulation of the MUL1-HSPA5 axis can be a novel strategy for the treatment of HNC.